2022
DOI: 10.3390/biom12091314
|View full text |Cite
|
Sign up to set email alerts
|

Digital Pathology: New Initiative in Pathology

Abstract: Digital pathology (DP) is an emerging field of pathology that manages information generated from digitized specimen slides [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…By reaching intraclass correlation coefficient values similar to those in the IKWG study, they proved that the artificial intelligence-based automated Ki-67 scoring method may be used to achieve good reproducibility compared to pathologists [9,10]. Furthermore, a comparative analysis of the visual assessment and automated digital image analysis of the Ki-67 index in breast cancer was performed by Zhong et al [11] and found a significant degree of consistency between both methods [11].…”
Section: Introductionmentioning
confidence: 74%
“…By reaching intraclass correlation coefficient values similar to those in the IKWG study, they proved that the artificial intelligence-based automated Ki-67 scoring method may be used to achieve good reproducibility compared to pathologists [9,10]. Furthermore, a comparative analysis of the visual assessment and automated digital image analysis of the Ki-67 index in breast cancer was performed by Zhong et al [11] and found a significant degree of consistency between both methods [11].…”
Section: Introductionmentioning
confidence: 74%
“…B. Mib1/Ki-67-Färbung). Heutzutage haben die meisten PathologInnen ihre Ausbildung unter Einsatz des konventionellen Lichtmikroskops abgeschlossen, daher stellt dieses nach wie vor den Goldstandard in der histopathologischen Diagnostik dar [ 17 , 18 ]. Um eine optimale digitale Transformation zu erreichen, ist daher eine enge Zusammenarbeit zwischen den PathologInnen und dem technischen Team unerlässlich.…”
Section: Umstellungsprozess Im Labor Und Bei Der Befundung Notwendigunclassified